2021
DOI: 10.1093/ehjci/jeab030
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular systolic function in severe tricuspid regurgitation: prognostic relevance of longitudinal strain

Abstract: Aims  The aim of this study is to analyse the prognostic implications of right ventricular (RV) dysfunction as detected by strain analysis in patients with severe tricuspid regurgitation (TR). The evaluation of RV systolic function in presence of severe TR is of paramount importance for operative risk stratification; however, it remains challenging, as conventional echocardiographic indexes usually lead to overestimation. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The effect of RV function in patients with valvular disease has been investigated in the last several years and it has become evident that effect of RV dysfunction on outcome in these patients is not irrelevant. The majority of studies reported deterioration of RV longitudinal strain in patients with valvular diseases (61, 62), but some recent investigations revealed a significant predictive value of RV strain in patients with aortic stenosis, mitral and tricuspid regurgitation (12,13,40,63). Data are still scarce but warrant a special attention due to constantly increasing number of transcatheter interventions in valvular diseases and importance to develop new scores for better risk stratification in patients who undergo these interventions.…”
Section: Rv Strain In Valvular Heart Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of RV function in patients with valvular disease has been investigated in the last several years and it has become evident that effect of RV dysfunction on outcome in these patients is not irrelevant. The majority of studies reported deterioration of RV longitudinal strain in patients with valvular diseases (61, 62), but some recent investigations revealed a significant predictive value of RV strain in patients with aortic stenosis, mitral and tricuspid regurgitation (12,13,40,63). Data are still scarce but warrant a special attention due to constantly increasing number of transcatheter interventions in valvular diseases and importance to develop new scores for better risk stratification in patients who undergo these interventions.…”
Section: Rv Strain In Valvular Heart Diseasesmentioning
confidence: 99%
“…Investigation that enrolled 250 consecutive patients with severe tricuspid regurgitation investigated RV global and freewall longitudinal strain and reclassified ∼42-56% of patients with normal RV systolic function according to conventional parameters in patients with impaired RV systolic function (13). The authors found that RV free-wall strain >-17% at baseline predicted RV heart failure, whereas patients with RV free-wall strain <-14% at follow-up had significantly better survival (13) (Table 4).…”
Section: Romano Et Al (44) 544mentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced free-wall RV longitudinal strain was superior predictor of mortality in comparison with reduced FAC (<35%) and TAPSE in the whole population [36]. Ancona et al involved only patients with severe TR who were mostly presented with symptoms of RV heart failure and advanced NYHA class [6]. The authors used freewall and global RV longitudinal strain for reclassification Fig.…”
Section: Right Ventricular Remodeling and Its Predictive Importance In Ftrmentioning
confidence: 99%
“…FTR is associated with significant remodeling of the right ventricle (RV), which includes the impairment of RV mechanical function, dilatation, and ultimately systolic dysfunction [6,7]. FTR has been also related with further changes in tricuspid valve anatomy (annular dilatation, higher level of tethering, and tenting) and right atrial (RA) dilatation, which altogether induce the lack of coaptation and deterioration of FTR grade [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%